2018
DOI: 10.1029/2017jc013584
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Near‐Inertial Currents on the Mid‐Atlantic Bight by Hurricane Arthur (2014)

Abstract: Near‐inertial currents (NICs) were observed on the Mid‐Atlantic Bight (MAB) during the passage of Hurricane Arthur (2014). High‐frequency radars showed that the surface currents were weak near the coast but increased in the offshore direction. The NICs were damped out in 3–4 days in the southern MAB but persisted for up to 10 days in the northern MAB. A Slocum glider deployed on the shelf recorded two‐layer baroclinic currents oscillating at the inertial frequency. A numerical model was developed to interpret … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…CC BY 4.0 License. Umlauf and Burchard (2003) for detailed description), a widely employed model that demonstrated good performance in simulating various oceanographic processes (Olabarrieta et al, 2011;Toffoli et al, 2012;Zhang et al, 2018).…”
Section: Basic Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…CC BY 4.0 License. Umlauf and Burchard (2003) for detailed description), a widely employed model that demonstrated good performance in simulating various oceanographic processes (Olabarrieta et al, 2011;Toffoli et al, 2012;Zhang et al, 2018).…”
Section: Basic Equationsmentioning
confidence: 99%
“…Shown in Figure 3a is the vertical profile of the seawater temperature measured by Glider RU16 launched off the New Jersey Coast. Glider RU16 was an autonomous underwater vehicle of the Slocum glider platform developed by Teledyne-Webb Research (Schofield et al, 2007(Schofield et al, , 2010, which has demonstrated to be advantageous in marine monitoring, particularly under extreme weather conditions (Glenn et al, 2016;Miles et al, 2017;Seroka et al, 2016;Zhang et al, 2018). Glider RU16 can measure not only the vertical profiles of seawater temperature and salinity but also the water depth.…”
Section: Effect Of Hurricane On Vertical Stratification and Sea Surfa...mentioning
confidence: 99%
See 2 more Smart Citations
“…In open ocean regions, hurricane impacts include the mixing of deeper water properties into the surface layer, direct air-sea exchange of moisture and heat from the sea surface, and the generation of near-inertial currents and surface and internal waves (e.g., Price 1981;Shay et al 1990Shay et al , 1992Sanford et al 2011;D'Asaro et al 2014;Zhang et al 2016). On continental shelves, hurricanes can cause coastal upwelling (or downwelling) (e.g., Smith 1982), rapid shelf-wide cooling (e.g., Zambon et al 2014;Glenn et al 2016;Seroka et al 2017), and near-inertial currents (e.g., Teague et al 2007;Shen et al 2017;Zhang et al 2018). In nearshore and coastal regions, hurricanes can induce strong currents, waves, and storm surges (e.g., Zheng 2006b, 2008;Dietrich et al 2010;Yang et al 2014;Marsooli and Lin 2018).…”
Section: Introductionmentioning
confidence: 99%